PENGARUH PENGALAMAN AUDITOR, TEKANAN KETAATAN, DAN TEKANAN ANGGARAN WAKTU TERHADAP AUDIT JUDGEMENT DENGAN KOMPLEKSITAS TUGAS SEBAGAI VARIABEL MODERASI DI KANTOR AKUNTAN PUBLIK SEMARANG - Mutia Rachma Syafitri, 14.05.52.0254; Badjuri, Achmad (Students' Journal of Accounting and Banking, 2018)
This research aims to determine the influence of auditor experience, pressure of obedience and time budget pressure on audit judgement with task complexity as a moderating variable. The population of this research are all auditors who work at Public Accounting Firm in Semarang. Sampling is done by using convenience sampling method and the number of samples was 83 respondents. The primary data collection method using questionnaire. Data is analyzed using the multiple linear regression analysis and absolute difference value test to analyze the influence of moderating variable by SPSS 21. The results show that auditor experience has no significant effect on the audit judgement, pressure of obedience has a significant negative effect on the audit judgement, meanwhile time budget pressure has positive significant effect on the audit judgement. Task complexity can’t moderate the influence of auditor experience, pressure of obedience and time budget pressure on audit judgement. Keywords: Audit judgement, auditor experience, pressure of obedience, time budget pressure, task complexity